Home Ownership Dynamics: Analysis of The Impact of Gold, Bonds and Stocks on Property Investment Moderated by Loan Interest Rates - Yoewono, Harsono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to examine how shares, bonds, and gold affect real estate investment, which is influenced by loan interest rates. In this study, the data type used is quantitative. Secondary data in the form of residential property price index data, bonds, stocks, loan interest rates and gold prices were sourced from Bank Indonesia. On a monthly basis, sampling employed a time series data method. Multiple linear regression is the data analysis technique employed in this study, which makes use of the E-views software. The study's findings indicate that gold has little bearing on real estate investments. Bonds have an impact on real estate investing. This demonstrates how interest rates or the inclination to invest in real estate can be impacted by an increase in bonds. Increase in shares can influence the interest or tendency to invest in property. Loan interest rates cannot moderate the influence of gold on property investment. Loan interest rates can moderate the effect of bonds on property investment. The results of this research show that there is a negative correlation, meaning that loan interest rates can weaken the influence of bonds on property investment. Loan interest rates can moderate the influence of shares on property investment. The results of this research show that there is a negative correlation, meaning that loan interest rates can weaken the influence of shares on property investment.